The factors affecting the financial performance in Malaysian palm oil industry - Norzaleha Binti, Ambo Tajang (Universiti Malaysia Sarawak, 2011)
This paper examines the factors affecting the financial performance in Malaysian Palm oil industry for five years starting in 2005 until 2009. Additionally, this study also identifies the determinants of financial performance in Malaysian palm oil industry.